Efficacy of raw milk preservation by aqueous extracts of Tulsi (Ocimum sanctum) and Neem (Azadirachta indica) - Khan, Sadia Afrin; Islam, Md. Zakirul; Islam, Mohammad Ashiqul; Siddiki, Mohammad Shohel Rana; Harun-ur-Rashid, Md. (Journal of the Bangladesh Agricultural University, 2020)
The study was aimed at assessing the effect of herbal plant leaves aqueous extract in prolonging the shelf-life of raw cow milk. Tulsi (Ocimum sanctum) and Neem (Azadirachta indica) were selected based on phytochemical analysis for the presence of phenolic compounds. The presence of phenolic compounds in the leaves extracts were confirmed qualitatively. Initial physicochemical and sensory attributes of raw cow milk were also performed. Both 1.25 and 1.5% Tulsi extract treated samples were found to be of normal yellowish-white color up to 19 h of storage. On the contrary, the 1.5% Neem extract was found to show the same color at 19 h of preservation. A significant difference (p<0.05) was found in the acidity, pH and clot-on-boiling (COB) test among the samples. The most acceptable acidity was found up to 14 h at the concentration of 0.75, 1.25 and 1.5% of Tulsi extract. In the case of Neem extract, the satisfactory acidity was noted for 1.25% concentration up to 17 h of storage. The most agreeable pH (6.5 to 6.8) of raw milk was recorded for 1.5% Tulsi and 1.5% Neem extract up to 17 h and 18 h, respectively. A concentration of 1.25% and 1.5% Neem extract was recorded as COB negative up to 15 h and 16 h of preservation, respectively. In response to microbial analysis, the lowest number of the total viable bacterial count was recorded for 1.25% Tulsi and 1.5% Neem extract with 3.79±0.87 and 3.62±0.90 log10CFU/mL. In conclusion, comparing the Tulsi and Neem extract in response to raw milk preservation both Tulsi and Neem extracts can be used with 1.5% concentration for up to 17 h of storage at room temperature. J Bangladesh Agril Univ 18(2): 449–455, 2020 https://doi.org/10.5455/JBAU.78613